A critical inquiry into the absence of a gender equality discourse in the coverage of the land redistribution issue in two Zimbabwean newspapers, The Daily News and The Herald, between 01 February and 30 June 2000 - Mawarire, Jealousy Mbizvo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2008)
The media, which help define what we think and our roles in the society, have a crucial role to project both men and women's issues so as to change people's perceptions and stereotypes about the role men and women play in the society. There is need, therefore, to ensure gender equality in the operations of the media so that issues to do with both men and women get adequate and equal coverage. This study on the reportage of the land redistribution exercise in Zimbabwe has, however, exposed the gendered nature of the operations of the media, particularly in the news production process. It provides that, overally, the news discourse is a masculine narrative whose androcentric form is a result of, and is protected by, claims to 'objectivity,' 'professionalism', 'impartiality' and the pursuit of a journalistic routine system that hegemonically prioritises men's issues over those of women. The situation, as the research shows, has not been helped by journalists' incapacity to do thematic appreciation of issues and their over-inclination towards a simplistic event-based journalism that fails to question policies as they are enacted and implemented in gender-skewed processes. The lack of gender policies, the operations of patriarchy and the pursuit of a journalistic routine system that sees nothing wrong with the ostracisation of women issues are very fundamental findings that the research uses in its attempts to explain why the gender equality discourse was left out of the news reports about the land reform exercise in Zimbabwe.
Keywords: The Daily News (Zimbabwe); The Herald (Zimbabwe); Journalism -- Zimbabwe; Mass media -- Social aspects -- Zimbabwe; Sex in mass media -- Zimbabwe; Discourse analysis -- Social aspects